REASONS WHY THE HUSBAND CHOSE VASECTOMY IN FAMILY PLANNING PARTICIPATION IN BENGKULU CITY - Prasiska Dwi Anggraeni; Heni Nopianti; Ika Pasca Himawati (SOSIOEDUKASI, 2026)
Indonesia’s high rapid population growth requires birth control through the Family Planning (KB) program, but contraceptive use is still mostly borne by women, while male participation, such as vasectomy, remains low due to social stigma and negative perceptions about masculinity. Therefore, the phenomenon of husbands choosing vasectomy in Bengkulu City is interesting to examine from a sociological perspective. This study aims to analyze the reasons why husbands in Bengkulu City choose vasectomy in participating in the family planning program. The study used a qualitative phenomenological approach with purposive sampling of seven informants who had undergone vasectomy, collecting data through in-depth interviews, observations, and documentation, which were then analyzed descriptively using Blau’s social exchange theory. The results showed that husbands chose vasectomy due to sense of responsibility toward their wives, having enough children, economic considerations, and the desire to share family planning roles, supported by adequate knowledge, partner support, and health worker information, although they still faced obstacles such as negative public perceptions and assumptions that vasectomy reduces masculinity. The implications based on the results of this study confirm that the decision to undergo a vasectomy is influenced by social, economic, and cultural factors, not solely medical considerations.